Update on the ethical, legal and technical challenges of translating xenotransplantation - Thom, Rebecca (Journal of medical ethics, 2024)
This manuscript reports on a landmark symposium on the ethical, legal and technical challenges of xenotransplantation in the UK. King’s College London, with endorsement from the British Transplantation Society (BTS), and the European Society of Organ Transplantation (ESOT), brought together a group of experts in xenotransplantation science, ethics and law to discuss the ethical, regulatory and technical challenges surrounding translating xenotransplantation into the clinical setting. The symposium was the first of its kind in the UK for 20 years. This paper summarises the content of the expert lectures showcasing the progress which has been made in xenotransplantation including—the history of xenotransplantation, advances in gene edited animals and progress towards clinical xenotransplantation. We then set out the ethical and legal issues still to be resolved. Finally, we report the themes of the roundtable discussion highlighting areas of consensus and controversy. While the detail of the legal discussion was directed towards the UK, the principles and summary reported here are intended to be applicable to any jurisdiction seeking to implement clinical xenotransplantation.